A glass fiber chopped strand mat emulsion adhesive and preparation method thereof
By using specific combination components and preparation methods in glass fiber chopped felt emulsion adhesives, the problem of difficult winding and short-lasting bonding strength of the adhesive in the prior art is solved, and the effect of high softness and easy winding is achieved, which is suitable for a variety of construction needs.
Patent Information
- Application Number
- CN202411957677.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
Existing glass fiber chopped felt emulsion adhesives are difficult to soften when rolled, the bonding strength is not long-lasting, and the hardness is high during construction, so they are not suitable for making special-shaped parts.
A glass fiber chopped felt emulsion adhesive with high softness and easy to roll is prepared by using a combination of components including water, butyl acrylate, vinyl acetate, reactive plasticizer, cosolvent, protective colloid, non-ionic emulsifier, oxidant and reducing agent.
It achieves durability of bonding strength, reduces the pressure sensitivity of the adhesive, improves the flexibility and processing convenience of the material, and is suitable for construction in various shapes.
Smart Images

Figure BDA0005216311040000131 
Figure BDA0005216311040000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a glass fiber chopped strand mat emulsion adhesive and a preparation method thereof. Background Art
[0002] Glass fiber chopped strand mat emulsion binder is an adhesive used to bind chopped strands of glass fibers together to form a mat-like material. It is usually an emulsion-like polymer, and its main components include various synthetic resin emulsions. For example, commonly used ones include acrylic emulsions and styrene acrylic emulsions. Acrylic emulsions have good adhesion, weather resistance and chemical stability; styrene acrylic emulsions combine the hardness of styrene and the flexibility of acrylic esters, and can provide better physical properties for chopped strand mats.
[0003] There are two methods of use: impregnation and spraying. The impregnation method is to immerse the glass fiber chopped strand mat in the emulsion adhesive so that the adhesive fully penetrates into the fiber gaps of the chopped strand mat. The impregnation time depends on factors such as the thickness of the mat and the viscosity of the adhesive, generally ranging from a few minutes to tens of minutes. Then, the excess adhesive is removed by extrusion or centrifugation, and then dried and cured. For some chopped strand mat products with complex shapes or large areas, the emulsion adhesive can be evenly sprayed on the surface of the chopped strand mat by spraying. After spraying, proper drying and curing treatment is required to ensure that the adhesive is completely cured and a good bonding effect is formed. The finished product can be used as a reinforcing material to enhance the material's tensile strength, flexural strength and other mechanical properties, and can improve the material's impact resistance. It can be used in the fields of building insulation core materials, waterproof membranes, and insulation materials for electronic equipment.
[0004] Most of the emulsion adhesives available on the market are polyvinyl acetate emulsions. One type is an emulsion with a higher Tg, which contains more vinyl acetate and has a higher tensile strength. It can meet the construction requirements of epoxy resin impregnation and is not easy to break. However, the produced glass fiber felt is difficult to roll up, which increases the transportation volume. The hardness is high during the construction process, which is not convenient for making special-shaped parts. The other type is an emulsion with a low Tg, which contains more butyl acrylate and is easy to roll up, but has poor tensile strength and is easy to break during the construction process. Although adding the functional monomer hydroxyethyl acrylate to the low Tg product helps to improve the bonding strength, it increases the polymer molecular weight, resulting in reduced product flexibility, and will cause serious back-adhesion of the felt cotton after rolling up, and the felt surface is easily damaged during the unfolding process.
[0005] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention
[0006] In view of the above-mentioned deficiencies of the prior art, the object of the present invention is to provide a glass fiber chopped strand mat emulsion adhesive having high softness, easy winding, and long-lasting bonding strength, and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A glass fiber chopped strand mat emulsion adhesive comprises the following components, calculated by weight: 100 parts of water, 60-80 parts of butyl acrylate, 60-80 parts of vinyl acetate, 1-5 parts of reactive plasticizer, 2-5 parts of cosolvent, 1-3 parts of protective colloid, 25-40 parts of nonionic emulsifier, 1-2 parts of oxidant, 1-2 parts of reducing agent and 1-2 parts of molecular weight regulator.
[0009] The glass fiber chopped strand mat emulsion adhesive, wherein the reactive plasticizer is diallyl phthalate or dibutyl maleate.
[0010] The glass fiber chopped strand mat emulsion adhesive, wherein the co-solvent is one or more of diethylene glycol butyl ether, ethylene glycol butyl ether, and butanediol butyl ether.
[0011] The glass fiber chopped strand mat emulsion adhesive, wherein the protective colloid is one or more of polyvinyl alcohol, hydroxymethyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose.
[0012] The glass fiber chopped strand mat emulsion adhesive, wherein the nonionic emulsifier is one of fatty alcohol polyoxyethylene ether, tridecyl alcohol ethoxylate, and alkyl polyoxyethylene ether.
[0013] The glass fiber chopped strand mat emulsion adhesive, wherein the oxidant is one of sodium persulfate, ammonium persulfate and potassium persulfate.
[0014] The glass fiber chopped strand mat emulsion adhesive, wherein the reducing agent is sodium bisulfite or ferrous sulfate.
[0015] The glass fiber chopped strand mat emulsion adhesive, wherein the molecular weight regulator is n-dodecyl mercaptan or iso-dodecyl mercaptan.
[0016] A method for preparing a glass fiber chopped strand mat emulsion adhesive comprises the following steps:
[0017] S1. According to the above parts by weight, butyl acrylate, reactive plasticizer, cosolvent are added to an emulsifying tank and stirred to dissolve; vinyl acetate and a molecular weight regulator are added to the emulsifying tank and stirred thoroughly;
[0018] S2. Take 5% of the total amount of nonionic emulsifier and the above parts by weight of protective colloid dissolved in the above parts by weight of water and transferred to the reactor, the reactor was heated to 85 ~ 90 ℃ with stirring, and then cooled to 60 ~ 65 ℃;
[0019] S3. 8 to 10% of the total mass of the mixture obtained in step S2 and 50% of the oxidant and the reducing agent are added to the reactor, and the reaction is carried out at 65 to 70 ° C for 0.5 to 1 hour with continuous stirring;
[0020] S4. Maintaining the temperature of the reactor at 65 to 70 ° C, adding dropwise the remaining mixture in step S2 and 30% of the oxidizing agent and the reducing agent, and controlling the addition time to 5 to 8 hours;
[0021] S5. After the addition is completed, the reactor is heated to 75-78 ° C and kept warm for 1 to 2 hours;
[0022] S6. Continue to add the remaining 20% of the oxidant and reducing agent, cool the reactor to 70 to 73 ° C, and keep warm for 10 to 20 minutes;
[0023] S7. Continue to cool the reactor to 40-50° C., add the remaining 95% of the nonionic emulsifier, stir evenly, and obtain the glass fiber chopped strand mat emulsion adhesive as described in any one of claims 1-8.
[0024] The preparation method of the glass fiber chopped strand mat emulsion adhesive, wherein the radius of the glass fiber chopped strand mat emulsion adhesive is 1000-2000nm; and the glass transition temperature is -25°C to -15°C.
[0025] Beneficial effects:
[0026] The present invention provides a glass fiber chopped strand mat emulsion adhesive and a preparation method thereof, which has the following advantages over the prior art:
[0027] 1. Compared with the commercially available chopped strand mat latex adhesive, the present invention uses a reactive plasticizer as an internal plasticizing monomer, which can solve the problem of decreased bonding strength caused by the overflow of the later added external plasticizer due to aging of the adhesive. Moreover, the reactive plasticizer has a higher plasticizing effect than soft monomers such as butyl acrylate or isooctyl acrylate, and a softer performance can be obtained at the same addition amount, and the pressure sensitivity of the obtained adhesive is lower.
[0028] 2. The present invention uses polyvinyl alcohol and cellulose with the smallest molecular weight as protective colloids, which can effectively reduce the viscosity of the reaction process and prevent the monomer from entering the interior of the polymer for reaction due to the high viscosity of the emulsion. In addition, the protective colloid with a small molecular weight can form more micelles, which can better protect the emulsion with large particles.
[0029] 3. The glass transition temperature of the latex adhesive designed by the present invention is low. The average molecular weight of the latex is reduced by a molecular weight regulator, and then a non-ionic emulsifier is added to make the latex have hot-melt properties after film formation. Since the molecular weight of the latex is small and the latex contains a large amount of small molecule emulsifiers, the emulsifier reduces the van der Waals force between the latex particles during the film formation process. Therefore, the latex dry film slowly melts into a semi-solid state at above 80°C, and the latex dry film melts into a liquid at 150°C. This characteristic is conducive to the latex adhesive penetrating into the interior of the chopped strand mat for bonding during the gluing process, thereby improving the bonding strength.
[0030] 4. The present invention adds ether cosolvents, which can increase the solubility of the reactive plasticizer in water, effectively increase the copolymerization efficiency of the reactive plasticizer and vinyl acetate-butyl acrylate, and thus increase the particle size of the emulsion. DETAILED DESCRIPTION
[0031] The present invention provides a glass fiber chopped strand mat latex binder and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail by the following examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.
[0032] The invention provides a glass fiber chopped strand mat emulsion adhesive, which comprises the following components, calculated by weight: 100 parts of water, 60-80 parts of butyl acrylate, 60-80 parts of vinyl acetate, 1-5 parts of reactive plasticizer, 2-5 parts of cosolvent, 1-3 parts of protective colloid, 25-40 parts of nonionic emulsifier, 1-2 parts of oxidant, 1-2 parts of reducing agent and 1-2 parts of molecular weight regulator.
[0033] Water is the dispersion medium of the emulsion system. It can disperse other water-insoluble organic components (such as butyl acrylate, vinyl acetate, etc.) in the form of tiny droplets to form an emulsion. In the emulsion polymerization process, the presence of water can effectively control the temperature of the reaction system, because water has a large specific heat capacity and can absorb the heat released by the polymerization reaction to avoid excessively high reaction temperatures.
[0034] Butyl acrylate is an important soft monomer, and its polymer chain has good flexibility, which enables the latex adhesive to give glass fiber chopped strand mat a certain degree of softness after curing. At the same time, the molecular structure of butyl acrylate contains ester groups, which can provide good viscosity, enhance the bonding force between the adhesive and the glass fiber, and help the chopped strand mat maintain structural integrity during subsequent processing and use. The addition of butyl acrylate can also reduce the glass transition temperature of the adhesive system. The lower Tg value makes the adhesive have better elasticity and viscosity at room temperature, which is more suitable for materials such as glass fiber chopped strand mat that require a certain degree of flexibility.
[0035] Vinyl acetate is a hard monomer, and its addition can increase the hardness and cohesion of the emulsion adhesive. After polymerization, the polymer chain segments of vinyl acetate can be intertwined with the chain segments of butyl acrylate to form a network structure with a certain strength, so that the adhesive can better withstand external forces after curing, and prevent the glass fiber chopped strand mat from deforming or the fibers from spreading when stretched or squeezed. In addition, vinyl acetate polymer has a certain hydrophobicity, which helps to improve the water resistance of the emulsion adhesive. When the glass fiber chopped strand mat is used in some environments that may be exposed to water (such as building waterproofing, shipbuilding and other fields), the water resistance can ensure that the performance of the chopped strand mat is not affected by moisture, thereby extending the service life of the product.
[0036] The above-mentioned emulsion adhesive uses a reactive plasticizer as an internal plasticizing monomer, which can react chemically with the polymer chain and be embedded between the polymer molecular chains, which can solve the problem that the existing post-added external plasticizer overflows due to the aging of the adhesive, causing the bonding strength of the product to decrease. Moreover, the reactive plasticizer has a higher plasticizing effect than the existing soft monomers such as butyl acrylate or isooctyl acrylate. Its addition can increase the spacing between the molecular chains and reduce the interaction between the molecular chains, thereby making the adhesive softer and easier to process after curing. In addition, the product can obtain softer performance at the same addition amount, and the pressure sensitivity of the obtained adhesive is better. In a low temperature environment, ordinary emulsion adhesives may become hard and brittle, while reactive plasticizers can reduce this effect. They can make the adhesive still maintain a certain elasticity and viscosity at a lower temperature, expanding the application temperature range of glass fiber chopped strand mat.
[0037] The addition of cosolvents can improve the solubility of some insoluble components in water, or enhance the compatibility between different components. For example, in the emulsion polymerization process, cosolvents can help non-ionic emulsifiers to be better dispersed in water, and also help dissolve and disperse organic monomers such as butyl acrylate and vinyl acetate, so that the polymerization reaction can proceed more evenly. It can also be used to adjust the viscosity of emulsion adhesives.
[0038] Protective colloids mainly form a protective film by adsorbing on the surface of emulsion droplets to prevent the aggregation of emulsion droplets. During the emulsion polymerization process, storage and use, this protective film can keep the emulsion stable and avoid stratification, demulsification and other phenomena. It can also be used to change the rheological properties of the emulsion, increase the viscosity of the emulsion, make the emulsion adhesive have better adhesion on the surface of the glass fiber, enable the emulsion adhesive to better wrap the glass fiber and improve the bonding effect.
[0039] Nonionic emulsifier is a key component in the emulsion polymerization process. It can reduce the surface tension of the oil-water interface, so that oily monomers such as butyl acrylate and vinyl acetate can form a stable emulsion in water. The molecular structure of the emulsifier has a hydrophilic head and a hydrophobic tail. Under stirring, it can wrap up the oily monomer and disperse it in water to form tiny droplets, providing a place for polymerization reaction. The size and distribution of polymer particles in the emulsion can also be controlled by adjusting the amount and type of nonionic emulsifier, increasing the stability of the emulsion, and in the processing of glass fiber chopped strand mat, it can penetrate more evenly between glass fibers to improve the uniformity and strength of bonding.
[0040] During the emulsion polymerization process, the oxidation-reduction initiation system composed of an oxidant and a reductant can generate free radicals to initiate the polymerization reaction of monomers such as butyl acrylate and vinyl acetate. Compared with the traditional thermal initiation method, the oxidation-reduction initiation system can initiate polymerization at a lower temperature, which is very beneficial for controlling reaction conditions, avoiding monomer volatilization and improving the efficiency of the polymerization reaction. By adjusting the amount of the oxidant and the reductant, the polymerization rate and the molecular weight of the generated polymer can be controlled to a certain extent.
[0041] Molecular weight regulators can regulate the molecular weight of polymers during the polymerization process. They can react with growing polymer chains to terminate the chain growth process, thereby controlling the molecular weight of the polymer. Appropriate molecular weight can balance the viscosity, fluidity and cohesion of the emulsion adhesive.
[0042] Specifically, the reactive plasticizer is diallyl phthalate or dibutyl maleate.
[0043] The molecular structure of diallyl phthalate (DAP) contains benzene rings and ester groups. During the emulsion polymerization process, DAP can participate in the polymerization reaction, and its molecular chain can be embedded in the polymer main chain formed by butyl acrylate and vinyl acetate. This embedding effect increases the spacing between the polymer molecular chains and enhances the mobility of the molecular chains, so that the emulsion adhesive has better flexibility after curing. In addition, the benzene ring structure in DAP gives the polymer a certain rigidity and stability, which can improve the chemical corrosion resistance and weather resistance of the emulsion adhesive. Furthermore, during the polymerization process or in the subsequent curing process, it can undergo a cross-linking reaction with the unsaturated bonds on the butyl acrylate and vinyl acetate polymer chains. This cross-linking reaction can form a three-dimensional network structure, improve the cohesion and strength of the emulsion adhesive, which enables the glass fiber chopped strand mat to better maintain its structural integrity when stretched or sheared by external forces, and the fibers will not easily separate.
[0044] The molecular structure of dibutyl maleate (DBM) contains ester groups and double bonds. The ester groups can increase the lubricity between molecular chains, making the polymer chains easier to slide, thereby improving the flexibility of the latex adhesive. In low-temperature environments, latex adhesives containing DBM can maintain good elasticity and viscosity. In addition, the double bonds in the DBM molecules can chemically react with active groups such as hydroxyl groups on the surface of glass fibers. At the same time, its ester groups can also interact with the polymer chains in the latex adhesive. This dual effect enables DBM to improve the wettability of the latex adhesive to the glass fibers, allowing the adhesive to better adhere to the surface of the glass fibers, thereby enhancing the bonding force.
[0045] The above two reactive plasticizers are both long molecular chain structures, which have a role in extending the polymer chain segments, and the resulting emulsion has excellent elongation. The increase in elongation has a good release effect on the stress generated when the chopped strand mat is rolled up, which can eliminate the phenomenon of drum surface caused by the high hardness of the glass fiber mat, and can effectively shorten the rolling radius of the chopped strand mat, thereby improving production efficiency.
[0046] Specifically, the cosolvent is one or more of diethylene glycol butyl ether, ethylene glycol butyl ether, and butylene glycol butyl ether. The cosolvent added is an ether cosolvent, which can be used as an intermediate solvent to increase the solubility of reactive plasticizers and nonionic emulsifiers that are difficult to dissolve in water in water, thereby effectively increasing the copolymerization efficiency of reactive plasticizers and vinyl acetate-butyl acrylate, and improving the particle size of the emulsion. In addition, when two or three of diethylene glycol butyl ether, ethylene glycol butyl ether, and butylene glycol butyl ether are used, they can play a synergistic role. Different cosolvents may have complementarity in regulating viscosity, and a cosolvent may mainly affect the initial viscosity of the emulsion at a lower concentration, while another cosolvent has a more obvious effect on the regulation of viscosity at a higher concentration.
[0047] Specifically, the protective colloid is one or more of polyvinyl alcohol, hydroxymethyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose. The hydroxyl groups on the molecular chains of PVA, HMC, HEC, and CMC can form hydrogen bonds with active groups such as hydroxyl groups on the surface of glass fibers. When the emulsion adhesive is used to bond glass fibers, the hydrogen bonding effect can enhance the bonding force between the adhesive and the glass fibers, and can also increase the flexibility of the emulsion adhesive to a certain extent. In addition, using polyvinyl alcohol and cellulose with the smallest molecular weight as protective colloids can effectively reduce the viscosity of the reaction process and prevent the monomer from being difficult to enter the internal reaction due to the high viscosity of the emulsion. In addition, small molecular weight protective colloids can form more micelles, which can better protect large-grained emulsions.
[0048] Specifically, the nonionic emulsifier is one of fatty alcohol polyoxyethylene ether, tridecyl alcohol ethoxylate, and alkyl polyoxyethylene ether. The above nonionic emulsifiers can utilize the hydrophilicity and hydrophobicity of their own chain segments to reduce the surface tension of the oil-water interface, disperse the oily monomer in water to form tiny emulsion droplets, and ensure that the polymerization reaction can be carried out evenly in the water phase. It can also be used to improve the stability of the emulsion and control the morphology and distribution of polymer particles in the emulsion, improve the wettability of the emulsion to glass fiber, and improve the processing performance of the emulsion.
[0049] Specifically, the oxidant is one of sodium persulfate, ammonium persulfate and potassium persulfate.
[0050] Specifically, the reducing agent is sodium bisulfite or ferrous sulfate.
[0051] Persulfate can decompose to generate free radicals, providing initiation active centers for emulsion polymerization, thereby initiating the polymerization reaction of monomers such as butyl acrylate and vinyl acetate. In the redox initiation system, the reducing agent and the oxidizing agent work together to react with the free radicals generated by the oxidizing agent to generate new free radicals with initiation activity, which can further initiate the polymerization reaction of the monomers.
[0052] Specifically, the molecular weight regulator is n-dodecyl mercaptan or iso-dodecyl mercaptan. Both n-dodecyl mercaptan and iso-dodecyl mercaptan are chain transfer agents, and both terminate the growth of polymer chains by participating in chain transfer reactions, thereby controlling the molecular weight of the polymer in the emulsion adhesive. Compared with n-dodecyl mercaptan, iso-dodecyl mercaptan, due to the difference in its molecular structure, will affect the chain structure and distribution of the polymer to a certain extent, thereby affecting the rheological properties, bonding properties, etc. of the emulsion adhesive.
[0053] The present invention also provides a method for preparing a glass fiber chopped strand mat emulsion adhesive, comprising the following steps:
[0054] S1. Add butyl acrylate, reactive plasticizer and cosolvent to the emulsification tank according to the above weight parts, and stir to dissolve, so that the components can be fully mixed and evenly formed to form a uniform organic phase system. Butyl acrylate is the main monomer component, and the reactive plasticizer can subsequently improve the flexibility and other properties of the adhesive, while the cosolvent helps them to better dissolve in each other and improve the dispersibility in water. Then add vinyl acetate and molecular weight regulator to the emulsification tank and stir well. Vinyl acetate is another important monomer, which participates in the subsequent polymerization reaction together with butyl acrylate. The two cooperate with each other to adjust the hardness, cohesion and other properties of the adhesive. The addition of molecular weight regulator is to intervene in advance so as to effectively control the molecular weight of the polymer in the subsequent polymerization process and ensure that the viscosity, fluidity and other properties of the final emulsion adhesive reach a suitable level.
[0055] S2. Take 5% of the total amount of nonionic emulsifier and the above-mentioned protective colloid by weight and dissolve them in the above-mentioned water by weight, and transfer them to the reactor, heat the reactor to 85-90°C and stir, and then cool it down to 60-65°C. The nonionic emulsifier begins to play its key role in emulsification here. Its partial addition can initially reduce the surface tension of the oil-water interface and prepare for the subsequent dispersion of the organic phase in the aqueous phase. After the protective colloid (such as polyvinyl alcohol, hydroxymethyl cellulose, etc.) is dissolved in water, on the one hand, it can stabilize the emulsion system formed subsequently and prevent the emulsion droplets from coalescing. On the other hand, it also helps to adjust the rheological properties of the emulsion so that it has a suitable consistency and is convenient for subsequent operations. High-temperature stirring helps to further evenly mix the various components, and at the same time fully dissolves and hydrates the protective colloid, etc., so as to better play its role in stabilizing the emulsion. The subsequent cooling to 60-65°C is to adjust the temperature in the reactor to a suitable range suitable for the start of the subsequent redox-initiated polymerization reaction, and avoid abnormal conditions such as excessively high temperature causing the reaction to be too intense.
[0056] S3. Add 8-10% of the total mass of the mixture obtained in step S2 and 50% of the oxidant and the reductant into the reactor, and react at 65-70°C for 0.5-1 hour with continuous stirring. The redox initiation system composed of the oxidant and the reductant begins to work at this temperature, and they react with each other to produce free radicals, initiating the polymerization reaction of monomers such as butyl acrylate and vinyl acetate. Adding only part of the mixture and half the amount of the oxidant and the reductant can allow the reaction to have a relatively mild start process, which is convenient for controlling the reaction rate.
[0057] S4. Keep the temperature of the reactor at 65-70°C, drip the remaining mixture in step S2 and 30% of the oxidant and reducing agent, and control the dripping time to 5-8 hours. On the basis that the reaction has been smoothly started, by slowly dripping the remaining raw materials, monomers and other reactants can be continuously and stably provided for the polymerization reaction, so that the polymerization reaction continues and the rate is relatively stable. Continuously adding a certain proportion of oxidants and reducing agents can continuously generate free radicals to maintain the growth of the polymerization chain. A longer dripping time helps to accurately control the progress of the reaction and the molecular weight distribution of the polymer, so that the performance of the final polymer is more uniform and stable, thereby ensuring that the emulsion adhesive has good comprehensive performance.
[0058] S5. After the addition is completed, heat the reactor to 75-78°C and keep it warm for 1-2 hours. The operation of heating and keeping warm is mainly to make the polymerization reaction more complete, to encourage the remaining monomers to participate in the polymerization reaction as much as possible, and to improve the monomer conversion rate. Keeping warm at a higher temperature for a certain period of time can make the polymerization reaction reach a relatively more complete level, ensure that the polymer component content in the emulsion adhesive is sufficient and the performance is stable, and avoid affecting the quality of the adhesive due to excessive monomer residues.
[0059] S6. Continue to add the remaining 20% of the oxidant and reductant, cool the reactor to 70-73°C, and keep it warm for 10-20 minutes. The purpose of adding the oxidant and reductant again at this time is to further supplement the initiating free radicals and make the final improvement to the polymerization reaction to ensure that the molecular weight and other properties of the polymer meet the expected requirements. Cooling down and keeping warm for a short time is to make appropriate temperature adjustments in the later stage of the reaction so that the polymerization reaction ends smoothly and avoids the degradation of polymer properties due to excessive temperature or excessive reaction.
[0060] S7. Continue to cool the reactor to 40-50°C, add the remaining 95% of the non-ionic emulsifier, stir evenly, and obtain the glass fiber chopped strand mat emulsion adhesive. The purpose of cooling to this temperature range is to cool the reaction system down, facilitate subsequent operations, and ensure the stability of the emulsion adhesive. Finally, add most of the remaining non-ionic emulsifier, mainly to further adjust the stability and emulsification effect of the emulsion, so that it has better dispersibility and storage stability, and also to optimize the rheological properties of the emulsion, etc., to ensure that the obtained emulsion adhesive can meet the requirements of its bonding performance, stability, etc. during the production process of glass fiber chopped strand mat.
[0061] Specifically, the radius of the glass fiber chopped strand mat emulsion adhesive is 1000-2000nm; the glass transition temperature is -25℃~-15℃. The prepared emulsion product has a low glass transition temperature. The average molecular weight of the emulsion is reduced by a molecular weight regulator, and then a non-ionic emulsifier is added to make the emulsion have hot-melt properties after film formation. Since the molecular weight of the emulsion is small and the emulsion contains a large amount of small molecule emulsifiers, the emulsifier reduces the van der Waals force between the latex particles during the film formation process. Therefore, the emulsion dry film slowly melts into a semi-solid state at above 80℃, and the emulsion dry film melts into a liquid at 150℃. This feature is conducive to the emulsion adhesive penetrating into the interior for bonding during the gluing process of the chopped strand mat, thereby improving the bonding strength. If there is no hot-melt property, the chopped strand mat will be delaminated during the winding process because the wrinkle stress cannot be released, which reduces the bonding strength. That is, the temperature of the chopped strand mat is still around 60℃ when it is wound, and the emulsion adhesive can correct the bonding situation according to the shape of the chopped strand mat.
[0062] In order to further illustrate a glass fiber chopped strand mat emulsion adhesive and a preparation method thereof provided by the present invention, the following examples are provided.
[0063] Example 1
[0064] A glass fiber chopped strand mat emulsion adhesive comprises the following components, calculated by mass: 100 parts of water, 70 parts of butyl acrylate, 75 parts of vinyl acetate, 4 parts of dibutyl maleate, 2 parts of polyvinyl alcohol BP-03, 2 parts of diethylene glycol butyl ether, 30 parts of tridecyl alcohol ethoxylate, 0.5 parts of ammonium persulfate, 0.5 parts of sodium bisulfite and 0.4 parts of n-dodecyl mercaptan.
[0065] The preparation method of the glass fiber chopped strand mat emulsion adhesive comprises the following steps:
[0066] S1. Add butyl acrylate, reactive plasticizer and cosolvent into an emulsifying tank according to the above weight parts, and stir to dissolve for 30 minutes, then add vinyl acetate and n-dodecyl mercaptan into the emulsifying tank and stir well.
[0067] S2. Take 5% of the total amount of tridecyl alcohol ethoxylate and the above-mentioned parts by weight of polyvinyl alcohol BP-03 and dissolve them in the above-mentioned parts by weight of water, and transfer them to a reactor, heat the reactor to 90°C and stir for 1 hour, and then cool to 65°C.
[0068] S3. Add 8-10% of the total mass of the mixture obtained in step S2 and 50% of ammonium persulfate and sodium bisulfite into the reactor, react at 65° C. for 1 hour with continuous stirring.
[0069] S4. Keep the temperature of the reactor at 65°C, add the remaining mixture in step S2 and 30% of the oxidant and the reducing agent, and control the addition time to 6 hours; sample the emulsion particle size every 1 hour during the addition process, and control the addition speed according to the particle size.
[0070] S5. After the addition is completed, the reactor is heated to 75°C and kept warm for 1.5 hours.
[0071] S6. Continue to add the remaining 20% of ammonium persulfate and sodium bisulfite, cool the reactor to 72°C, and keep warm for 15 minutes.
[0072] S7. The reaction kettle is further cooled to 40° C., and the remaining 95% of tridecyl alcohol ethoxylate is added and stirred evenly to obtain the glass fiber chopped strand mat emulsion adhesive.
[0073] Example 2
[0074] A glass fiber chopped strand mat emulsion adhesive comprises the following raw materials, measured by mass: 100 parts of water, 80 parts of butyl acrylate, 65 parts of vinyl acetate, 5 parts of dibutyl maleate, 3 parts of hydroxyethyl cellulose (Ashland 250LR), 2 parts of diethylene glycol butyl ether, 28 parts of fatty alcohol polyoxyethylene ether, 1 part of sodium persulfate, 1 part of sodium bisulfite and 0.4 parts of n-dodecyl mercaptan.
[0075] Example 3
[0076] A glass fiber chopped strand mat emulsion adhesive comprises the following raw materials, measured by mass: 100 parts of water, 70 parts of butyl acrylate, 70 parts of vinyl acetate, 3 parts of diallyl phthalate, 3 parts of carboxymethyl cellulose, 3 parts of butanediol butyl ether, 28 parts of fatty alcohol polyoxyethylene ether, 0.5 parts of ammonium persulfate, 0.5 parts of ferrous sulfate and 0.3 parts of n-dodecyl mercaptan.
[0077] Example 4
[0078] A glass fiber chopped strand mat emulsion adhesive comprises the following raw materials, measured by mass: 100 parts of water, 80 parts of butyl acrylate, 75 parts of vinyl acetate, 3 parts of diallyl phthalate, 2 parts of hydroxymethyl cellulose, 5 parts of ethylene glycol butyl ether, 32 parts of alkyl polyoxyethylene ether, 1 part of potassium persulfate, 1 part of sodium bisulfite and 0.3 parts of isododecyl mercaptan.
[0079] Performance Testing
[0080] According to the national standard GB / T 17470-2007, the main test indicators of glass fiber chopped strand mat are tensile strength at break, styrene dissolution rate, penetration rate in unsaturated polyester, and flexural strength.
[0081] Among them, the tensile strength test reflects the bonding strength of the adhesive, the styrene dissolution rate and the penetration rate in unsaturated polyester also reflect the dissolution rate of the adhesive, and the bending strength characterizes its softness, which is mainly affected by the glass transition temperature of the adhesive.
[0082] Experimental test: The adhesive prepared in Examples 1-4 of the present invention was used to produce 300 g / m 2 The standard weight of glass fiber chopped strand mat was tested for tensile strength according to GB / T6006.2-2003, styrene solubility according to GB / T6006.1-2003, unsaturated polyester penetration rate according to the target ring method, and bending strength according to the inclined plane method of GB / T18318.1-2009. The obtained data are shown in Table 2 below.
[0083] Table 1 shows the basic properties of the emulsions obtained in each embodiment.
[0084]
[0085] Table 2 is the properties of glass fiber chopped strand mat produced by the adhesive of the present invention
[0086]
[0087] It can be seen from the above data that the chopped strand mat produced in the present invention has a low glass transition temperature, and the flexural strength shows that the chopped strand mat has excellent flexibility. The chopped strand mat has a soft feel, is easy to roll up, and is convenient for construction, and its tensile strength can reach or exceed the national standard.
[0088] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the present invention.
Claims
1. A glass fiber chopped strand mat emulsion adhesive, characterized in that: Calculated by weight, the composition includes: 100 parts of water, 60 to 80 parts of butyl acrylate, 60 to 80 parts of vinyl acetate, 1 to 5 parts of reactive plasticizer, 2 to 5 parts of cosolvent, 1 to 3 parts of protective colloid, 25 to 40 parts of nonionic emulsifier, 1 to 2 parts of oxidant, 1 to 2 parts of reducing agent and 1 to 2 parts of molecular weight regulator.
2. The glass fiber chopped strand mat emulsion adhesive according to claim 1, characterized in that: The reactive plasticizer is diallyl phthalate or dibutyl maleate.
3. The glass fiber chopped strand mat emulsion adhesive according to claim 1, characterized in that: The co-solvent is one or more of diethylene glycol butyl ether, ethylene glycol butyl ether, and butanediol butyl ether.
4. The glass fiber chopped strand mat emulsion adhesive according to claim 1, characterized in that: The protective colloid is one or more of polyvinyl alcohol, hydroxymethyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose.
5. The glass fiber chopped strand mat emulsion adhesive according to claim 1, characterized in that: The nonionic emulsifier is one of fatty alcohol polyoxyethylene ether, tridecyl alcohol ethoxylate, and alkyl polyoxyethylene ether.
6. The glass fiber chopped strand mat emulsion adhesive according to claim 1, characterized in that: The oxidant is one of sodium persulfate, ammonium persulfate and potassium persulfate.
7. The glass fiber chopped strand mat emulsion adhesive according to claim 1, characterized in that: The reducing agent is sodium bisulfite or ferrous sulfate.
8. The glass fiber chopped strand mat emulsion adhesive according to claim 1, characterized in that: The molecular weight regulator is n-dodecyl mercaptan or iso-dodecyl mercaptan.
9. A method for preparing a glass fiber chopped strand mat emulsion adhesive, characterized in that: The steps include: S1. According to the above parts by weight, butyl acrylate, reactive plasticizer, cosolvent are added to an emulsifying tank and stirred to dissolve; vinyl acetate and a molecular weight regulator are added to the emulsifying tank and stirred thoroughly; S2. Take 5% of the total amount of nonionic emulsifier and the above parts by weight of protective colloid dissolved in the above parts by weight of water and transferred to the reactor, the reactor was heated to 85 ~ 90 ℃ with stirring, and then cooled to 60 ~ 65 ℃; S3. 8 to 10% of the total mass of the mixture obtained in step S2 and 50% of the oxidant and the reducing agent are added to the reactor, and the reaction is carried out at 65 to 70 ° C for 0.5 to 1 hour with continuous stirring; S4. Maintaining the temperature of the reactor at 65 to 70 ° C, adding dropwise the remaining mixture in step S2 and 30% of the oxidizing agent and the reducing agent, and controlling the addition time to 5 to 8 hours; S5. After the addition is completed, the reactor is heated to 75-78 ° C and kept warm for 1 to 2 hours; S6. Continue to add the remaining 20% of the oxidant and reducing agent, cool the reactor to 70 to 73 ° C, and keep warm for 10 to 20 minutes; S7. Continue to cool the reactor to 40-50° C., add the remaining 95% of the nonionic emulsifier, stir evenly, and obtain the glass fiber chopped strand mat emulsion adhesive as described in any one of claims 1-8.
10. The method for preparing the glass fiber chopped strand mat emulsion adhesive according to claim 9, characterized in that: The radius of the glass fiber chopped strand mat latex adhesive is 1000-2000nm; and the glass transition temperature is -25°C--15°C.